Pelatihan Jurnalistik Siswa-Siswi Madrasah Aliyah Negeri (MAN) 2 Mataram, Nusa Tenggara Barat (NTB) - Moh Hafizni (Jurnal Pemberdayaan: Publikasi Hasil Pengabdian Kepada Masyarakat, 2025)
Journalism training is also considered important, not only for high school students but also for all groups, including the general public and teachers. The challenge of this community service is to equip students with accurate and professional journalistic knowledge and to present media content that adheres to journalistic codes of ethics while using language that is understandable by the audience. This community service aims to equip students of Madrasah Aliyah Negeri (MAN) 2 Mataram with good and correct journalistic knowledge. In addition, students can present media content that complies with journalistic codes of ethics and language that is understandable to the audience. This community service research employs a descriptive qualitative research method, focusing on the approach of interpersonal communication theory. The community service, in the form of journalism training, was attended by approximately 80 participants from MAN 2 Mataram students, who also served as research subjects in this community service. The results of the study show that teachers and students participating in the MAN 2 Mataram journalism training are aware and consider that journalism training is essential, not only for high school students (SMA) but also for all groups, including the general public. Even the teachers consider that journalism training needs to be provided to teachers so that they can understand journalistic practices correctly and adequately. The audience will be able to comprehend the work of journalists in the field and simultaneously distinguish between accurate and inaccurate information.